Phosphorus-based p-type thermoelectric conversion material and thermoelectric conversion element using the same

By performing composite doping of Cu and Ga in Ag6Ge10P12, the structure and electronic structure of the phosphide matrix p-type thermoelectric conversion material are optimized, and the problem of insufficient thermoelectric performance of existing materials is solved, and higher thermoelectric performance and environmental friendliness are achieved.

JP7665175B2Active Publication Date: 2025-04-21TOKYO METROPOLITAN IND TECH RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2020182067
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-30
Publication Date
2025-04-21
Estimated Expiration
2040-10-30

AI Technical Summary

Technical Problem

The thermoelectric properties of existing phosphide matrix p-type thermoelectric conversion materials in medium and low temperature regions have not yet reached the level of traditional Bi-Te and Pb-Te materials, and the effect of improved element doping is limited.

Method used

By performing composite doping in Ag6Ge10P12 and doping Cu and Ga elements at Ag and Ge sites, respectively, the structure and electronic structure of the compound are optimized to improve its thermoelectric properties.

Benefits of technology

It is possible to significantly improve the output factor and thermoelectric ratio (ZT) of thermoelectric materials in medium and low temperature areas, while reducing resistivity and thermal conductivity, and improving the environmental friendliness of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665175000001
    Figure 0007665175000001
  • Figure 0007665175000002
    Figure 0007665175000002
  • Figure 0007665175000003
    Figure 0007665175000003
Patent Text Reader

Abstract

To provide a phosphorus-based p-type thermoelectric conversion material and a thermoelectric conversion element using the same having less environmental load and having better thermoelectric characteristics than before.SOLUTION: In a thermoelectric conversion material consisting of a phosphorus-based compound represented by a chemical formula of Ag6-xAxGe10-yByP12, in the above chemical formula, the A site is at least one element selected from the group consisting of Li, Na, K, Rb, Cs, Cu, and Au, and the B site is at least one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Al, Ga, In, Tl, Sb, and Bi.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a phosphorus-based p-type thermoelectric conversion material and a thermoelectric conversion element using the same. [Background technology]

[0002] Thermoelectric materials are materials that directly convert thermal energy into electrical energy through the movement of conductive carriers inside the material. The temperature difference generated across the two ends of a thermoelectric material by heat can be directly converted into electrical energy through a phenomenon called the Seebeck effect.

[0003] Thermoelectric conversion materials have long been attracting attention for their applications in waste heat power generation and Peltier cooling, and in recent years have also been attracting attention from the perspective of their use in energy harvesting, which makes use of unused waste heat, as emergency power sources in the event of a disaster, and as independent power sources for IoT sensors.

[0004] Among such thermoelectric conversion materials, Bi-Te-based materials and Pb-Te-based materials are known as representative thermoelectric conversion materials in the medium to low temperature range. However, these materials contain rare elements or harmful elements such as Te, Pb, and Se, which limits their application in consumer applications. In response to this, the phosphorus-based compound Ag6Ge 10 P 12 At present, it has attracted attention as an environmentally friendly thermoelectric material that has excellent thermoelectric properties among phosphorus-based compounds in the medium to low temperature range and does not contain any highly toxic harmful elements.

[0005] However, it is difficult to say that phosphorus-based thermoelectric conversion materials have sufficient thermoelectric performance comparable to conventional materials such as Bi-Te-based materials and Pb-Te-based materials. 10 P 12 Attempts have been made to further improve thermoelectric performance by doping impurities into the Ag or Ge sites of the above-mentioned materials, thereby reducing thermal conductivity and maximizing the power factor by optimizing the carrier density (see, for example, Non-Patent Documents 1 and 2). [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] H. Namiki and Y. Ota, Jpn. J. Appl. Phys. 59, 075508 (2020). [Non-Patent Document 2] X. Shen, Y. Xia, G. Wang, F. Zhou, V. Ozolins, X. Lu, G. Wang, and Z. Zhou, J. Mater. Chem. A, 6, 24877 (2018). Summary of the Invention [Problem to be solved by the invention]

[0007] Here, the performance of a thermoelectric conversion material is expressed by the dimensionless figure of merit (ZT), which is expressed by the general formula: ZT = S 2 It is calculated by T / (ρκ) (S is the Seebeck coefficient, T is the absolute temperature, ρ is the electrical resistivity, and κ is the thermal conductivity). In the above formula, a good thermoelectric conversion material must have a large Seebeck coefficient, a small electrical resistivity, and a small thermal conductivity. 2 / ρ is called the power factor and corresponds to the amount of power generated.

[0008] In Non-Patent Document 1, Cu is doped into the Ag site to form Ag6Ge 10 P 12 It has been reported that the thermal conductivity decreases with an increase in the Cu content, but the power factor does not increase because of the increase in electrical resistivity caused by the scattering of conduction carriers, and the increase in ZT is slight.

[0009] On the other hand, in Non-Patent Document 2, Ga is doped into the Ge site, 10 P 12 It has been reported that Ag6Ge 10 P 12In the compound, Ga ions act as hole dopants, decreasing the electrical resistivity and increasing the power factor. However, due to the increase in thermal conductivity caused by impurities, the increase in ZT is small, as in Non-Patent Document 1.

[0010] Thus, Ag6Ge 10 P 12 has relatively high thermoelectric properties among phosphorus-based compounds in the medium-low temperature range, and is attracting attention as a thermoelectric conversion material with a low environmental impact that does not contain highly toxic harmful elements, but at present, it is difficult to say that it has sufficient thermoelectric performance comparable to conventional Bi-Te and Pb-Te materials. In addition, the element doping currently reported for the purpose of improving thermoelectric properties only improves performance slightly, so there is a strong demand for the development of materials that can achieve further performance improvements and the development of thermoelectric conversion elements using these materials.

[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a phosphorus-based p-type thermoelectric conversion material that has a low environmental impact and superior thermoelectric properties compared to conventional materials, and a thermoelectric conversion element using the same. [Means for solving the problem]

[0012] In order to achieve the above object, the present inventors have developed a phosphorus-based compound, Ag6Ge 10 P 12 By reducing the electrical resistivity, the power factor can be maximized while the thermal conductivity can be reduced, and as a result, the inventors have been working hard to achieve even better thermoelectric properties. In the process, the inventors discovered that a composite substitution composition in a specific phosphorus compound can achieve excellent thermoelectric properties, and have completed the present invention.

[0013] That is, the phosphorus-based p-type thermoelectric conversion material of the present invention has the following chemical formula: Ag 6-x A x Ge 10-y B y P 12A phosphorus-based compound thermoelectric conversion material represented by the following chemical formula, wherein in the chemical formula, the A site is at least one element selected from the group consisting of Li, Na, K, Rb, Cs, Cu, and Au, and the B site is at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Al, Ga, In, Tl, Sb, and Bi. Second, in the phosphorus-based p-type thermoelectric conversion material of the first invention, it is preferable that 0 < x ≦ 0.2 and 0 < y ≦ 0.25 in the chemical formula. Third, in the phosphorus-based p-type thermoelectric conversion material of the first or second invention, it is preferable that 0 < x + y ≦ 0.5 in the chemical formula. Fourth, in the phosphorus-based p-type thermoelectric conversion material of the first to third inventions, it is preferable that x is 0.15 to 0.17 in the chemical formula. Fifth, in the phosphorus-based p-type thermoelectric conversion material of the first to fourth inventions, it is preferable that y is 0.10 to 0.125 in the chemical formula. Sixth, in the phosphorus-based p-type thermoelectric conversion material of the first to fifth inventions, it is preferable that the A site in the chemical formula is Cu and the B site is Ga. Seventh, the thermoelectric conversion element of the present invention is characterized by using the phosphorus-based p-type thermoelectric conversion material of the first to sixth inventions.

Advantages of the Invention

[0014] According to the present invention, there are provided a phosphorus-based p-type thermoelectric conversion material having excellent thermoelectric properties, which contains no harmful elements, has a low environmental load, reduces the thermal conductivity while maximizing the output factor by reducing the electrical resistivity, and a thermoelectric conversion element using the same.

Brief Description of the Drawings

[0015] [Figure 1] It is a graph showing the X-ray diffraction patterns of Ag6-xCuxGe10-yGayP12 (x = 0.15, 0.17; y = 0.052, 0.10, 0.25) obtained in Examples 1 to 3 and Ag6Ge10P12 obtained in the comparative example. [Diagram 2] 1 is a graph showing the temperature dependence of electrical resistivity (ρ) of Ag6-xCuxGe10-yGayP12 (x=0.15, 0.17; y=0.052, 0.10, 0.25) obtained in Examples 1 to 3 and Ag6Ge10P12 obtained in Comparative Example. [Diagram 3] 1 is a graph showing the temperature dependence of the Seebeck coefficient (S) of Ag6-xCuxGe10-yGayP12 (x=0.15, 0.17; y=0.052, 0.10, 0.25) obtained in Examples 1 to 3 and Ag6Ge10P12 obtained in Comparative Example. [Figure 4] 1 is a graph showing the temperature dependence of the power factor (S2 / ρ) of Ag6-xCuxGe10-yGayP12 (x=0.15, 0.17; y=0.052, 0.10, 0.25) obtained in Examples 1 to 3 and Ag6Ge10P12 obtained in the comparative example. [Diagram 5] 1 is a graph showing the temperature dependence of thermal conductivity (κ) of Ag6-xCuxGe10-yGayP12 ((x=0.15, 0.17; y=0.052, 0.10, 0.25) obtained in Examples 1 to 3 and Ag6Ge10P12 obtained in Comparative Example. [Figure 6] 1 is a graph showing the temperature dependence of the dimensionless figure of merit (ZT) of Ag6-xCuxGe10-yGayP12 (x=0.15, 0.17; y=0.052, 0.10, 0.25) obtained in Examples 1 to 3 and Ag6Ge10P12 obtained in the comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment of a phosphorus-based p-type thermoelectric conversion material according to the present invention will be described.

[0017] The phosphorus-based p-type thermoelectric material of the present invention has the chemical formula Ag 6-x A x Ge 10-y B y P 12In the chemical formula, the A site is at least one element selected from the group consisting of Li, Na, K, Rb, Cs, Cu, and Au, and the B site is at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Al, Ga, In, Tl, Sb, and Bi.

[0018] The phosphorus-based p-type thermoelectric material of the present invention is Ag6Ge 10 P 12 The assumption is that multiple element substitution is performed on Ag. 6-x A x Ge 10-y B y P 12 The compound element substitution is represented by the formula: In the above formula, specific impurities are doped in specific amounts as the A site and B site to improve the thermoelectric properties.

[0019] The thermoelectric properties of thermoelectric conversion materials are expressed by the dimensionless figure of merit (ZT), and are expressed by the general formula: ZT=S 2 T / (ρκ), where S is the Seebeck coefficient (VK -1 ), ρ is electrical resistivity (Ωm), κ is thermal conductivity (Wm -1 K -1 ), T is absolute temperature (K). Also, S 2 / ρ(Wm -1 K -2 ) is called the power factor and corresponds to the amount of electricity generated. In order to improve the dimensionless figure of merit, a thermoelectric conversion material must satisfy the conditions of a large Seebeck coefficient, a small electrical resistivity, and a small thermal conductivity.

[0020] The above chemical formulaAg 6-x A x Ge 10-y B y P 12In this case, the A site is at least one element selected from the group consisting of Li, Na, K, Rb, Cs, Cu, and Au. By using at least any one atom of the above group as the atom of the A site, the thermal conductivity can be mainly decreased. Further, Cu is particularly preferable as the atom of the A site, and by doping Cu, the effect of particularly decreasing the thermal conductivity compared to other atoms can be obtained.

[0021] Also, in the above chemical formula Ag 6-x A x Ge 10-y B y P 12 In this case, the B site is at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Al, Ga, In, Tl, Sb, and Bi. By using at least any one atom of the above group as the atom of the B site, the electrical resistivity can be decreased and the output factor can be increased. Further, Ga is particularly preferable as the atom of the B site, and by doping Ga, the effect of particularly increasing the output factor compared to other atoms can be obtained.

[0022] Also, in the case of the composite substitution in the phosphorus-based p-type thermoelectric conversion material of the present invention, in the above chemical formula Ag 6-x A x Ge 10-y B y P 12 x is preferably in the range of 0 < x ≤ 0.2, more preferably 0.15 to 0.17. Also, y is preferably in the range of 0 < y ≤ 0.25, more preferably 0.10 to 0.125. Further, in the above chemical formula, it is preferable that 0 < x + y ≤ 0.5.

[0023] In the above chemical formula Ag 6-x A x Ge 10-y B y P 12 By doping x and y in the above chemical formula under the above conditions, undoped Ag6Ge 10 P 12Compared to the conventional method, the electrical resistivity (ρ) can be lowered and the power factor (S 2 / ρ) can be increased. Also, the thermal conductivity (κ) can be decreased. This increases the dimensionless figure of merit (ZT), i.e., improves the thermoelectric properties.

[0024] The method of composite substitution in the present invention can be carried out by pulverizing and mixing each material component in a preset stoichiometric ratio with an excess of P, vacuum sealing the mixture in a container, and then melting the mixture in an electric furnace.

[0025] In this way, the phosphorus-based p-type thermoelectric conversion material of the present invention can increase the output factor and reduce the thermal conductivity by complex-substituting a plurality of the constituent elements with a specific element, thereby enabling the development of excellent thermoelectric properties. In addition, since the phosphorus-based p-type thermoelectric conversion material of the present invention does not contain harmful elements, it can be a thermoelectric conversion material with a small environmental impact.

[0026] In addition, in the present invention, the phosphorus-based p-type thermoelectric conversion material can be used to provide a thermoelectric conversion element. By using the thermoelectric conversion element of the present invention, it is possible to provide a thermoelectric conversion device that contributes to the clean energy field, such as exhaust heat power generation, Peltier cooling, energy harvesting, emergency power supply in the event of a disaster, and independent power supply, as a device with low environmental impact and excellent thermoelectric properties. EXAMPLES

[0027] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0028] <Example 1> Ag, Cu, Ge, Ga in stoichiometric ratio and 3% excess P were crushed and mixed in a mortar, vacuum sealed in a quartz glass tube, and then melted in an electric furnace to obtain Ag. 5.85 Cu 0.15 Ge 9.9375 Ga 0.0625 P 12was synthesized (theoretical calculation values: x = 0.15, y = 0.0625).

[0029] Synthetic Ag 5.85 Cu 0.15 Ge 9.9375 Ga 0.0625 P 12 The composition of the sample was analyzed using an ICP emission spectrometer (iCAP 6500 DUO, manufactured by Thermo Fisher Scientific). 5.85 Cu 0.15 Ge 9.948 Ga 0.052 P 12 (x=0.15, y=0.052).

[0030] Using an X-ray diffraction device (Rigaku SmartLab), the synthesized sample Ag 5.85 Cu 0.15 Ge 9.948 Ga 0.052 P 12 The crystal structure of (x=0.15, y=0.052) was confirmed, and the results are shown in Figure 1.

[0031] The temperature dependence of electrical resistivity ρ was measured using a physical property measurement system (Quantum Design PPMS: Physical Property Measurement System), and the results are shown in Figure 2. In addition, the temperature dependence of the Seebeck coefficient S was measured using the above-mentioned physical property measurement system (PPMS). The results are shown in Figure 3. The power factor S calculated using the measured electrical resistivity ρ and Seebeck coefficient S 2 The temperature dependence of / ρ is shown in Figure 4.

[0032] Furthermore, the temperature dependence of thermal conductivity κ was measured using the above physical property measurement system (PPMS), and the results are shown in Figure 5. Figure 6 shows the temperature dependence of ZT calculated using the measured electrical resistivity ρ, Seebeck coefficient S, and thermal conductivity κ.

[0033] <Example 2> Ag, Cu, Ge, Ga in stoichiometric ratio and 3% excess P were crushed and mixed in a mortar, vacuum sealed in a quartz glass tube, and then melted in an electric furnace to obtain Ag. 5.85 Cu 0.15 Ge 9.875 Ga 0.125 P 12 was synthesized (theoretical calculation values: x = 0.15, y = 0.125).

[0034] Synthetic Ag 5.85 Cu 0.15 Ge 9.875 Ga 0.125 P 12 The composition of the sample was analyzed using an ICP emission spectrometer (iCAP 6500 DUO, manufactured by Thermo Fisher Scientific). 5.85 Cu 0.15 Ge 9.90 Ga 0.10 P 12 (x=0.15, y=0.10).

[0035] Sample Ag synthesized using an X-ray diffraction apparatus (Rigaku SmartLab) 5.85 Cu 0.15 Ge 9.90 Ga 0.10 P 12 The crystal structure of (x=0.15, y=0.10) was confirmed, and the results are shown in Figure 1.

[0036] The temperature dependence of electrical resistivity ρ was measured using a physical property measurement system (Quantum Design PPMS: Physical Property Measurement System), and the results are shown in Figure 2. In addition, the temperature dependence of the Seebeck coefficient S was measured using the above-mentioned physical property measurement system (PPMS). The results are shown in Figure 3. The power factor S calculated using the measured electrical resistivity ρ and Seebeck coefficient S 2 The temperature dependence of / ρ is shown in Figure 4.

[0037] Furthermore, the temperature dependence of thermal conductivity κ was measured using the above physical property measurement system (PPMS), and the results are shown in Figure 5. Figure 6 shows the temperature dependence of ZT calculated using the measured electrical resistivity ρ, Seebeck coefficient S, and thermal conductivity κ.

[0038] <Example 3> Ag, Cu, Ge, Ga in stoichiometric ratio and 3% excess P were crushed and mixed in a mortar, vacuum sealed in a quartz glass tube, and then melted in an electric furnace to obtain Ag. 5.85 Cu 0.15 Ge 9.75 Ga 0.25 P 12 was synthesized (theoretical calculation values: x = 0.15, y = 0.25).

[0039] Synthetic Ag 5.85 Cu 0.15 Ge 9.75 Ga 0.25 P 12 The composition of the sample was analyzed using an ICP emission spectrometer (iCAP 6500 DUO, manufactured by Thermo Fisher Scientific). 5.83 Cu 0.17 Ge 9.75 Ga 0.25 P 12 (x=0.17, y=0.25).

[0040] Sample Ag synthesized using an X-ray diffraction apparatus (Rigaku SmartLab) 5.83 Cu 0.17 Ge 9.75 Ga 0.25 P 12 The crystal structure of (x=0.17, y=0.25) was confirmed, and the results are shown in Figure 1.

[0041] The temperature dependence of electrical resistivity ρ was measured using a physical property measurement system (Quantum Design PPMS: Physical Property Measurement System), and the results are shown in Figure 2. In addition, the temperature dependence of the Seebeck coefficient S was measured using the above-mentioned physical property measurement system (PPMS). The results are shown in Figure 3. The power factor S calculated using the measured electrical resistivity ρ and Seebeck coefficient S 2 The temperature dependence of / ρ is shown in Figure 4.

[0042] Furthermore, the temperature dependence of thermal conductivity κ was measured using the above physical property measurement system (PPMS), and the results are shown in Figure 5. Figure 6 shows the temperature dependence of ZT calculated using the measured electrical resistivity ρ, Seebeck coefficient S, and thermal conductivity κ.

[0043] <Comparative Example> Ag, Ge, and 3% excess P in a stoichiometric ratio were crushed and mixed in a mortar, vacuum sealed in a quartz glass tube, and then melted in an electric furnace to obtain non-doped Ag6Ge. 10 P 12 was synthesized.

[0044] Sample Ag6Ge synthesized using an X-ray diffraction apparatus (Rigaku SmartLab) 10 P 12 The crystal structure of (x=0.0, y=0.0) was confirmed, and the results are shown in Figure 1.

[0045] The temperature dependence of electrical resistivity ρ was measured using a physical property measurement system (Quantum Design PPMS: Physical Property Measurement System), and the results are shown in Figure 2. In addition, the temperature dependence of the Seebeck coefficient S was measured using the above-mentioned physical property measurement system (PPMS). The results are shown in Figure 3. The power factor S calculated using the measured electrical resistivity ρ and Seebeck coefficient S 2 The temperature dependence of / ρ is shown in Figure 4.

[0046] Furthermore, the temperature dependence of thermal conductivity κ was measured using the above physical property measurement system (PPMS), and the results are shown in Figure 5. Figure 6 shows the temperature dependence of ZT calculated using the measured electrical resistivity ρ, Seebeck coefficient S, and thermal conductivity κ.

[0047] <Result> From FIG. 1, in Examples 1 to 3 and the Comparative Example, the parent phase, Ag6Ge 10 P 12 It was confirmed that the material had a crystal structure of 0.01μm and contained no impurity phase. In addition, as shown in Figures 2 and 3, the electrical resistivity and Seebeck coefficient decreased with increasing Ga doping amount, and it was confirmed that Ga contributed to the increase in hole carriers.

[0048] Furthermore, from Fig. 4, the power factor S calculated from the electrical resistivity and the Seebeck coefficient 2 / ρ is the chemical composition Ag 5.85 Cu 0.15 Ge 9.90 Ga 0.10 P 12 As shown in Fig. 5, the thermal conductivity decreases with the Ga doping amount, and 2 ZT, which can be calculated by T / (ρκ), is the chemical composition of Ag 5.85 Cu 0.15 Ge 9.90 Ga 0.10 P 12 At 390K, it reaches 0.38.

[0049] From the above Examples 1 to 3, it was confirmed that by complexly substituting a plurality of the constituent elements with appropriate elements, it is possible to increase the power factor and reduce the thermal conductivity, thereby providing excellent thermoelectric properties.

Claims

1. Chemical formula Ag 6-x A x Ge 10-y B y P 12 A thermoelectric conversion material comprising a phosphorus-based compound represented by the formula: In the above chemical formula, the A site is at least one element selected from the group consisting of Cu and Au. The B site is at least one element selected from the group consisting of Al, Ga, and In, x is 0.15≦x≦0.17, and y is 0.052≦y≦0.

25. A phosphorus-based p-type thermoelectric conversion material.

2. 2. The phosphorus-based p-type thermoelectric conversion material according to claim 1, wherein, in the chemical formula, x+y satisfies 0<x+y≦0.

5.

3. A thermoelectric conversion element using the phosphorus-based p-type thermoelectric conversion material according to claim 1 or 2.

Citation Information

Patent Citations

  • Thermoelectric semiconductor and manufacture thereof

    JP2001044520A

  • Thermoelectric conversion material, method of producing thermoelectric conversion material and thermoelectric conversion module

    JP2016058558A